ONTARGET: Treatment Nonadherence Rapidly Increases CV Event Risk - Jacobson, Anne (MD Conference Express, 2011)
Patients who are at high risk for cardiovascular events face a vicious cycle in which treatment nonadherence increases event rates while events themselves reinforce nonadherence, according to new findings from the Ongoing Telmisartan Alone and in Combination With Ramipril Global Endpoint Trial [ONTARGET].